The acceptability and efficacy of a brief universal preventive parenting intervention for child behavioural and emotional disorders - Foskolos, K (2015)
This thesis investigates the acceptability and efficacy of a brief universal preventive parenting intervention for child behavioural and emotional difficulties. The methodology included a systematic review, a literature review, a pilot randomised controlled trial and focus group discussions. The systematic review aimed to show whether behavioural and emotional difficulties are a significant problem in Greece. Greek children appeared to display high scores on, and prevalence of behavioural problems, compared to children from other countries. The results suggested that, based on parental reports, Greece seems to have a high prevalence in child behavioural and emotional difficulties. The literature review explored the effectiveness of universally delivered Triple P preventive interventions and identified research gaps. There was also insufficient evidence on the effectiveness of brief universal Triple P programmes to draw any definitive conclusions. No randomised trial had examined the short-term and long-term effectiveness of the Triple P brief universal interventions (Seminar Series). The pilot randomised trial explored the efficacy of the Triple P Seminar Series for the reduction of child behavioural and emotional difficulties. 124 parents were randomly allocated to receive three seminars on positive parenting, while parents in the control group received information on child development. There was a significant reduction in behavioural problems over time (primary outcome), and a reduction in parenting dysfunctional difficulties in the short-term. Parents gave positive feedback on the intervention indicating that overall it was acceptable, feasible, culturally relevant, and useful. Preliminary moderator analyses indicated that there were no moderator variables affecting the relation between group allocation and change in child disruptive scores. Preliminary mediator analyses suggested that a reduction in dysfunctional practices partially explained improvements in children’s disruptive behaviours over time. Lastly, 46 parents of the intervention group shared their personal experiences regarding the Seminar Series during six focus groups. The facilitators of positive parenting were relevant to what they did before, during, and after their practices, while barriers included child, parent and external factors. The final conclusions after triangulation and the implications of this thesis for practice and further research were discussed.